A Case Study Approach: Workplace Discrimination Influencing Employee Loyalty - Fang, Ze Lun (2010)
Employee loyalty is the key to organizations success. It became more important in the industries which contribute heavily to a country’s GDP. Malaysia is a developing country and it highly relies on manufacturing industry. Malaysia’s manufacturing industry has undergone many changes in the past few decades. Thus, researcher intended to explore the discriminatory factors that influencing employee loyalty in manufacturing industry. Career advancement, gender discrimination and disability discrimination are examined. Many previous researches have validated the discriminatory issues exits long time ago; it lower employee loyalty and additional costs incurred for the businesses. The researcher intended to examine the discriminatory factors and recommend the possible solutions to improve the employee loyalty models. This study can serve as a model to be adopted for years to come in the employee loyalty model in the manufacturing industry of Malaysia. The variables, specifically career advancement, gender discrimination and disability discrimination exist for years, through various industries. These factors will continue to be of use across the manufacturing industry and other industry across Malaysia.